Aspiracje migracyjne młodzieży akademickiej - Kozielska, Joanna (Kultura-Społeczeństwo-Edukacja, 2020)
The purpose of this article is to identify student migration plans. The presented data are included in the optics of comparing the migration aspirations of medical students and pedagogy (N = 289). The research sample of the entire project in quantitative analysis numbered 604 people, and it was students of Poznan universities: Adam Mickiewicz University; Poznan University of Technology; Medical University; Economic University; University of Arts in Poznań. External migrations of „white staff” are an important topic, for example, in public debates due to the wide context of consequences that may occur in an abandoned country, which is why this group was chosen as a reference group in relation to the group constituted by pedagogy students.